Cultivo e comercialização de produtos agrícolas em uma área de várzea no município de Benjamin Constant, Amazonas - Soares, Raquel Gomes (Brasil, 2023)
The present work aimed to analyze the management of cultivation and the conduction the commercialization of agricultural products used by family farmers in the Santa Luzia community, the field research used a qualitative and quantitative methodological approach. A bibliographic survey relevant to the proposed theme was carried out and observations were made. For data collection, a question form was applied, field research was carried out by collecting information in the community. The family farmers of Santa Luzia have the family as the responsible for the agricultural activity and over the years alternative ways have been contracted to minimize the problems arising from the seasonality of the rivers, in addition to planning the entire production process that goes from the stages of cultivation to the sale of products at fairs, local markets and for municipal public policy programs in the municipality of Benjamin Constant. Although there are still difficulties with regard to transportation and marketing of production. Therefore, the study on the cultivation and commercialization of agricultural products in the community located on a floodplain island, in the municipality of Benjamin Constant, specifically in Santa Luzia, is relevant because it represents an initiative capable of generating information about the cultivation and commercialization of agricultural products agricultural inputs, since there are few data in the region on this subject. In this way, this study will serve as a theoretical sport to support the discussion on the cultivation and commercialization of agricultural products produced by family farmers in the community of Santa Luzia in Benjamin Constant, Amazonas.